Beschäftigungsstrukturen ausländischer Arbeitskräfte in Österreich und Deutschland - Unterschiede und Gemeinsamkeiten - Fassmann, Heinz; Seifert, Wolfgang (ERDKUNDE, 1997)
The Austrian and German occupational systems concerning the employment of foreign labour are characterized by many common features. Both countries started with the systematic recruitment of foreign labour from southern and south-eastern Europe in the second half of the 50's or at the beginning of the 60's. Both pursued a policy of short-term working stays and the rotation of the recruited labour. And both defined specific branches of the labour market in which foreign citizens were allowed to work legally. In no way did Austria or Germany leave the employment of foreigners to the forces of the free market, but produced on the contrary a partially complicated set of rules that defines who is allowed to work when, to what extent and in what branches. This regulation had a large share in the formation of an ethnic labour market, which has had lasting effects on the employment situation of foreigners in Austria and Germany. This article presents an analysis of this ethnic segmentation of the labour market in Germany and Austria. It is based on several microcensuses and on the socioeconomic panel. Among other things the analysis proves that the German labour market gives foreigners of the second and third generation better professional chances than does the Austrian. Whereas a stronger fixation on professional entrance placements can be stated for Austria. Barriers of ethnic segmentation are in Germany easier to overcome than in Austria. Different explanatory approaches for this and other detectable differences are discussed in the present contribution.